Rheology of peach pulp-powdered activated carbon mixtures - Arslanoolu, Feride Naime; Kar, Filiz; Arslan, Nurhan (Springer India, 2009)
This study examined the rheologgical behaviour of peach pulp-powdered activated carbon mixtures (PPPACM) and validated the power-law model. A rotational viscometer was used to determine the theological properties of PPPACM. Operating parameters varied between 15 and 40 degrees C for temperature, 0.5 and 5 kg/m(3) for concentration, and 5 and 60 rpm for rotational speed. The apparent viscosity versus shear rate data for PPPACM exhibited shear-thinning characteristics and power-law model described well the apparent viscosity versus shear rate data of all samples. The addition of activated cat-boil in peach pulp, temperature and shear rate affected the rheological properties. The consistency coefficient and the flow behaviour index decreased with temperature. The consistency coefficient increased with activated carbon concentration but no harmonious variation observed at the flow behaviour index values with increase in activated carbon concentration. The apparent viscosity of PPPACM showed an increase with increasing activated carbon concentration. Empirical models to predict the apparent viscosity of PPPACM were developed.
Keywords: Peach pulp; Powdered activated carbon; Rheology; Apparent viscosity